OS MONSTROS E A QUESTÃO RACIAL - Magalhães, Célia Maria (Em Tese, 1998)
This paper aims at investigating monstrosity as a narrative construction in the nineteenth century English literary fantastic and in Brazilian modernist literature. It focuses on gothic and modernist monsters as constructs for the representation of otherness. In conclusion it claims that Oswald de Andrade's cannibal and Mário de Andrade's trickster are different counterdiscursive constructs, each signalling at particular cultural issues.